THE CORRELATION BETWEEN ANXIETY AND SPEAKING ABILITY OF THE SEVENTH GRADE STUDENTS OF SMP NEGERI 5 KEDIRI IN ACADEMIC YEAR 2021/2022 - Ni Ketut Ayu Kusumadeni; I Gusti Agung Putri Wirastuti; Luh Ketut Sri Widhiasih (Academic Journal on English Studies (AJOES), 2022)
Most students who are studying English have difficulty identifying general information, specific information, and textual meaning and reference because they lack vocabulary. Therefore, an appropriate and effective teaching strategy should enable the students to improve their reading comprehension. The present study attempts to find out if the reading comprehension of the eighth-grade students of SMP Negeri 3 Ubud in the academic year 2020/2021 could be improved through KWL strategy combined with pictures. This research made use of a classroom action design by running two cycles and each cycle consisted of two sessions. running two cycles and each cycle consisted of two sessions. This research was done in two cycles and each cycle consisted of two sessions. The research administered pre-test, post-test, and questionnaire in order to collect the data before they were analyzed. The findings of the research revealed that there were significant improvements in subjects' achievement from the pre-test and post-test. From the questionnaire that was administered in the last cycle, the students gained positive responses in terms of their changing learning behavior toward the application of KWL strategy. Based on the findings of the study, the student’s reading comprehension can be improved through KWL strategy combined with the picture.